MARINE-DERIVED COMPOUNDS FOR WOUND HEALING AND TISSUE REPAIR - TURAKULOV, RUSTAM; HOSSEIN, RAMI RYAD; IKROMJON KIZ, ABDURAKHIMOVA ZULAYKHO; KUMAR, MANI RAJA; DASH, MR. SMRUTI RANJAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Natural product medicine was outstanding in traditional and modern system of medicine throughout recent decades. The study primarily evaluates the wound healing activity and healing of infected wounds by V. arborea fractions from literature and traditional form alone. Screening required appropriate and laboratory model conforming to the 3Rs principle of animal experimentation. Accordingly, a novel, adult zebrafish excision wound model was developed to screen for both activities alone and simultaneously when wounds were infected with microbe (under compromised conditions). In recent times, there is again a renaissance for screening of herbal extracts for the discovery of safer and more efficient drugs. The assessment of the active ingredients and mode of action of different aquatic medicinal plants is now underway. For the purpose of managing and treating wounds, certain medicinal plants and herbs that have been shown to be beneficial in the healing process were selected. They are slow healing wounds and wound management has been one of the challenging tasks in some conditions.